Cassava (Manihot esculenta Crantz) - Ceballos, H.; Hershey, Clair H. (Springer, 2017)
Cassava is a key food security staple and a competitive feedstock for multiple industrial processes and end uses. Farmers grow hybrids which are reproduced vegetatively. Several programs have used the same breeding scheme for the last 40 years. Significant progress has been made, particularly with the first improved varieties released in the 1980s and 1990s. However, gains slowed down since then. Biotechnology tools, after more than two decades, have not yet had impact on increasing yields. Results from ongoing genomic selection show promising results for high-heritability traits, but not for fresh root yield (FRY). Key challenges to increase FRY are the strong influence of nonadditive genetic effects and the heterozygous nature of breeding parents. There is large within-family variation masking the true breeding value of each progenitor. To improve yields, breeding must shift from making crosses where breeders hope to find hybrids that are superior to those already available (a strategy that has made only slow progress in the last decade or two) to develop and improve inbred progenitors that can produce more reliably better hybrids. The use of inbred progenitors and implementation of reciprocal recurrent selection should be an efficient way to exploit heterosis and epistasis, which are large components in the determination of FRY. Induction of flowering would also accelerate genetic gains. In the near-term future, available molecular markers can be used to improve the breeding value of progenitors rather than in selection of segregating progenies. They can also be used to screen germplasm collections in search of useful traits.